Human Freedom and Economic Prosperity: Evidence from Eastern Europe - Makrevska Disoska, Elena; Shapkova Kocevska, Katerina (My University, 2019)
The main mechanism that relates human freedom to economic growth is channeled through institutional and economic factors, such as government effectiveness, investments, and trade. Therefore, institutions are an important determinant of economic prosperity in countries worldwide. Institutions shape human behavior, set the “rules of the game” in society, and reflect the prevailing norms and values. Both economic science and history have proved that economies and societies flourish in a market-supportive environment where institutions adhere to personal choice, self-ownership, and the rule of law. In this paper, we focus on exploring the fractional effects of institutional changes on economic growth (measured as GDP per capita) and on productivity (measured as GDP per person employed). We developed ordinary least squares (OLS) panel regression models for selected economies of Eastern Europe, or around 20 cross-section units (countries) in the period between 2008 and 2016. The cross-country regression models demonstrate that institutions presented with human freedom and human capital have the highest influence and are statistically significant determinants of economic growth and productivity in the selected economies of Eastern Europe.
Keywords: institutions, liberalism, human freedom, economic growth, Eastern Europe.